Rewritable Polymer Brush Micropatterns Grafted by Triazolinedione Click Chemistry. Issue 44 (8th September 2015) - Roling, Oliver; De Bruycker, Kevin; Vonhören, Benjamin; Stricker, Lucas; Körsgen, Martin; Arlinghaus, Heinrich F.; Ravoo, Bart Jan; Du Prez, Filip E.
Abstract: Triazolinedione (TAD) click reactions were combined with microcontact chemistry to print, erase, and reprint polymer brushes on surfaces. By patterning substrates with a TAD‐tagged atom‐transfer radical polymerization initiator (ATRP‐TAD) and subsequent surface initiated ATRP, it was possible to graft micropatterned polymer brushes from both alkene‐ and indole‐functionalized substrates. As a result of the dynamic nature of the Alder–ene adduct of TAD and indole at elevated temperatures, the polymer pattern could be erased while the regenerated indole substrate could be reused to print new patterns. To demonstrate the robustness of the methodology, the write–erase cycle was repeated four times. Abstract : Write and erase : The click reaction between a triazolinedione (TAD)‐conjugated ATRP initiator and indole was used for the patterning of glass and silicon wafers employing microcontact chemistry. The reversibility of the click reaction enabled the writing, erasing, and rewriting of surfaces with polymer brush micropatterns for the first time.